PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN IBU HAMIL TENTANG KEHAMILAN RISIKO TINGGI DI WILAYAH KERJA PUSKESMAS REJOSARI KOTA PEKANBARU - Trinanda, Lisa; Erika, Erika; Sari, Sabtria Winda; Rajagukguk, Sartika; Ramadhani, Dyah Wulan; Utami, Nurul (Ensiklopedia of Journal, 2024)
High-risk pregnancy is a pregnancy that causes danger and complications to the mother and fetus in the womb. Health education about high-risk pregnancy is important for the community, especially pregnant women. The purpose of this study was to determine the effect of health education using animated video media on pregnant women's knowledge about high-risk pregnancy in the Rejosari Health Center Working Area, Pekanbaru City. This study used a quasy experimental method with the design and design of one group pre-post test with a population of 65 people and the determination of the sample was determined by purposive sampling using the slovin formula as many as 39 pregnant women respondents. Data collection was done using a questionnaire. Analysis was carried out by univariate analysis and bivariate analysis using the Wilcoxon Non Parametric test. The statistical test results obtained a p-value of 0.000 <0.005, it can be concluded that there is an effect of health education using animated video media on the knowledge of pregnant women about high-risk pregnancy in the Rejosari Health Center Working Area, Pekanbaru City. It is expected that pregnant women can find out information about high-risk pregnancy through health education using animated video media.Keywords: Health Education, Animated Video, Pregnancy Knowledge High Risk